Clinico-Pathological Study of Neck Abscess in Diabetic Patients (The Insight, 2024)
Introduction: To study about the correlation between clinical and pathological features of neck abscess in diabetic patients. Methods & Materials: Non-randomized, prospective, cross sectional, observational study was carried out at Department of Otolaryngology of Shaheed Ziaur Rahman Medical College Hospital, Bogra, Bangladesh from April, 2018 to September, 2018. Total 50 cases of diabetic patients having neck abscess were selected by purposive sampling. Then history taking, clinical examinations, relevant investigations along with antibiogram were done in all cases. Afterwards data were collected by the preformed data collection sheet. Then data were recorded, compiled, edited and analyzed. Results: Out of 50 diabetic patients Dysphagia 33(66%) was the commonest symptom. Other symptoms were fever 24(48%), neck swelling 15(30%), neck pain 15(30%), toothache 10(20%) and respiratory difficulty 8(16%). On clinical examination commonly 40(80%) patient had neck swelling which was subsequently followed by oropharyngeal swelling 32(64%) and trismus 10(20%). About 23(46%), 16(32%), 8(16%) and 3(6%) developed neck abscess in submandibular space, parapharyngeal space, retropharyngeal space and parotid space respectively. Bacteria isolated from pus culture revealed Peptostreptococcus 4(8%) as common anaerobes followed by Bacteroids 1(2%). Common aerobic organisms include Klebsiella pneumoniae 25(50%) followed by Streptococci viridans 6(12%), Staphylococcus aureus 5(10%) and Pseudomonas 4(8%). Conclusion: Neck abscess in diabetic patients occurred commonly in male with lower socio-economic class. Dysphagia and neck swelling were the commonest symptom and sign respectively. In diabetic patients neck abscess occurred commonly in submandibular space. Klebsiella pneumoniae was the commonest aerobic organism whereas Peptostreptococcus was the frequent anaerobe.
Keywords: Neck Abscess; Diabetic Patients; Neck Swelling